Meningkatkan Perkembangan Berpikir Simbolik Anak Usia 4-5 Tahun Dengan Media Lesung Angka ( PTK Di PAUD Oryza Sativa Kabupaten Kepahiang) - Juliana, Lensi; Asnawati, Asnawati; Haryono, Mimpira (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The purpose of this study was to determine the increase in symbolic thinking in children using the number mortar media at PAUD Oryza Sativa, Kepahiang Regency. This study is a Classroom Action Research (CAR) or also called Classroom action research with the procedure used in the form of a cycle. The subjects of this study were children in group A at PAUD Oryza Sativa, Kepahiang Regency, totaling 20 children. The study was carried out in three cycles. Data analysis was carried out in qualitative and quantitative descriptions with the emphasis being used to determine the increase in the process expressed in a predicate, while quantitative analysis was used to determine the increase in results using percentages. The results of the increase in symbolic thinking skills in children using the number mortar media at PAUD Oryza Sativa, Kepahiang Regency in cycle I with a percentage of 31.87%, in cycle II with a percentage of 51.25%, and cycle III with a percentage of 85.31%. The conclusion of the study is that using number mortar media can improve symbolic thinking skills in children at PAUD Oryza Sativa, as proven in cycle III where there was an increase with a percentage of achievement of 85.31% with the criteria of developing very well (BSB).